Natriuretic Peptides: Biochemistry, Physiology, Clinical Implication - I. A. Kozlova; I. Ye. Kharlamova (Общая реаниматология, 2009)
In the past years, the interest of theorists and clinicians has steadily increased in the myocardially secreted hormones – natriuretic peptides. At the Congress of the European Society of Anesthesiology (Munich, 2007), B-type natriuretic peptides were included into the list of the parameters of perioperative laboratory monitoring that is expedient in the practice of anesthetists and resuscitation specialists. The literature review shows the history of discovery and identification of different types of natriuretic peptides and considers the matters of their biochemistry. It also details information on the synthesis, secretion, and clearance of these peptides, as well as their receptor apparatus in various organs and tissues. The physiology of the regulatory system is described, as applied to the cardiovascular, excretory, central nervous systems, and the neuroendocrine one. Special attention is given to the current publications on the control of B-type natriuretic peptides as biomarkers of cardiac dysfunction. The diagnostic and prognostic values of peptides are analyzed in chronic circulatory insufficiency, coronary heart disease, and other car-diological and non-cardiological diseases. The prognostic value of elevated B-type natriuretic peptide levels in cardiac surgery is separately considered. It is concluded that the changes in the level of B-type natriuretic peptides in different clinical situations are the subject of numerous researches mainly made in foreign countries. The bulk of these researches are devoted to the study of peptides in cardiology and other areas of therapy. Studies on the use of peptides in reanimatology are relatively few and their results are rather discordant. The foregoing opens up wide prospects for studying the use of B-type natriuretic peptides in Russian intensive care and anesthesiology. Key words: natriuretic peptides, brain nautriuretic peptides, NT-proBNP.